Redes sociais da internet e políticas públicas educacionais: influências recíprocas - Santos, Priscila Costa (2021)
This thesis aims to understand the influences of Internet Social Networks on the formulation of public policies in Education, in the light of the Actor-Network Theory, through the establishment of relationships between Education, Social Networks and Politics. The Cartography of Controversies is adopted as a methodological approach, electing as a field of analysis the public policy of the High School Reform in Brazil. The analyzed data involve: 1. comments present on the Social Network Twitter extracted through the Netlytic tool during the periods of greatest controversy – 11.25.2016 to 12.02.2016 and 02.08.2017 to 02.09.2017 – about the High School Reform 2. legal documents that conduct public policy and 3. information present in digital media. In the process of systematic literature review, the Social Networks Analysis through the Gephi software created Authors' Networks and Production Networks, by which process supported the definition of the categories of analysis used in the study. Data analysis is organized into four axes: the first axis presents the narrative of the High School Reform as a record of the periods of greatest dynamism and associations of actors; the second axis runs through the Diagram of Actors-networks of the High School Reform, which graphically represents the associations and compositions of actors-networks, human and non-human; the third axis; covers the results and analyzes from the Similarity and Cohesive Trees of the two periods of greatest controversy for this analysis, the Cohesive Hierarchical Implicative Classification (CHIC) software is used; the last axis presents an interrelation between the previously analyzed axes. In general terms, the results indicated that: 1. Social Networks are important actors in the formulation of public policies in Education, centering as a space for engagement and civic participation; 2. Social Networks reveal the distance between citizens and the feeling represented by public policy, political parties and/or government entities; and 3. the curriculum is considered an important element of micropolitical intervention, materializing itself as a field of dispute in which actors associate or distance themselves depending on their values and political positions. In view of these results, it is urgent to advance in studies involving the association between human and non-human actors, in particular, regarding Social Networks, it is necessary to deepen studies on the multiple faces that this actor can influence in the rise of a new form of action, civic participation and citizen voice